SPATIAL VARIABILITY OF LONGITUDINAL DISTRIBUTION OF CORN SEEDS IN FUNCTION OF THE DISPLACEMENT SPEED - Nascimento, Elivania Maria Sousa; Chioderoli, Carlos Alessandro; Amorim, Marcelo Queiroz; Oliveira, Jean Lucas Pereira; Lopes, José Evanaldo Lima (ENERGIA NA AGRICULTURA, 2019)
Spatial variability of longitudinal distribution of corn seeds in function of the displacement speed Elivânia Maria Sousa Nascimento1, Carlos Alessandro Chioderoli2, Marcelo Queiroz Amorim3, Jean Lucas Pereira Oliveira4, José Evanaldo Lima Lopes5 1 Departamento de Engenharia Agrícola, Universidade Federal do Ceará, Avenida Mister Hull, Bloco 804, s/n, Pici, 60455-760, Fortaleza, Ceará, Brasil, elivania_sousa@yahoo.com.br. 2 Curso de Agronomia, Universidade Federal do Triângulo Mineiro, Avenida Rio Paranaíba, 1229, 38280-000, Iturama, Minas Gerais, Brasil, ca.chioderoli@gmail.com. 3 Departamento de Engenharia Agrícola, Universidade Federal do Ceará, Avenida Mister Hull, Bloco 804, s/n, Pici, 60455-760, Fortaleza, Ceará, Brasil, mqueirozamorim@yahoo.com. 4 Faculdade de Ciências Agrárias e Veterinárias, Universidade Estadual Paulista, Via de Acesso Professor Paulo Donato Castellane, s/n, Jaboticabal São Paulo, 14884-900, jean07lucasagro@gmail.com. 5 Empresa de Assistência Técnica e Extensão Rural do Ceará, Avenida Bezerra de Menezes, 1900, São Gerardo, 60325-105, Fortaleza, Ceará, Brasil. evanaldolopes@yahoo.com.br. Abstract: In the seeding process, factors many interfere in the plants stand, among them, the longitudinal distribution of seeds as a function of displacement speed. So, objective of this study is to assess the spatial variability of the longitudinal distribution of corn seeds as a function of the displacement speed of the tractor seed-fertilizer. The experiment had conducted at the Federal University of Ceara, Fortaleza, Ceara, Brazil in an area 0.19 ha. The speeds were 4.59; 6.86 and 8.16 km h-1. The regularity of plants longitudinal distribution was determined 21 days after seeding, and within each point the distance between the corn plants in the central line of ten meters in length was measured, percentage of spacing between plants considered as acceptable, multiples and failures. The results showed that the displacement speed negatively influenced the longitudinal distribution of seeds for the normal spacing and positively of failures spacing. The spatial dependence analysis proved to be a useful tool to represent the behavior of the longitudinal distribution of seeds evaluated in sowing operation as a function of the displacement speed. Keywords: geostatistic, mechanization. production. Variabilidade espacial da distribuição longitudinal de sementes de milho em função da velocidade de deslocamento Resumo: No processo de semeadura, para se obter produtividades elevadas, inúmeros fatores interferem no estande de plantas, dentre estes, a distribuição longitudinal das sementes em função da velocidade de deslocamento. Assim objetivou-se com este trabalho estudar a variabilidade espacial da distribuição longitudinal de sementes de milho em função da velocidade de deslocamento do conjunto trator semeadora-adubadora. O experimento foi conduzido na Universidade Federal do Ceará, Fortaleza/CE em uma área de 0,19 ha. As velocidades de deslocamento utilizadas foram 4,59; 6,86 e 8,16 km h-1. A regularidade da distribuição longitudinal de plantas foi determinada 21 dias após a semeadura, sendo que, dentro de cada ponto procedeu-se a mensuração da distância entre as plantas de milho existentes na linha central de dez metros de comprimento, calculando o percentual de espaçamentos entre plantas, considerado em aceitáveis, múltiplos e falhos. Os resultados mostraram a velocidade de deslocamento influenciou negativamente na distribuição longitudinal de sementes para a classe de espaçamentos normal e positivamente na classe de espaçamentos falhos. A análise da dependência espacial demonstrou ser ferramenta útil para representar o comportamento da distribuição longitudinal de sementes avaliadas em operação de semeadura em função da velocidade de deslocamento. Palavras-chave: geoestatística, mecanização, produtividade.